A violência do discurso como estratégia de apagamento da existência dos sujeitos homossexuais - Neves, Raquel Gomes Ferreira (2022)
Leishmaniasis, caused by protozoa of the genus Leishmania spp., are infectious, neglected diseases, classified as zoonotic, which present themselves in two possible clinical forms, tegumentary and visceral, the latter being more serious and potentially fatal. These diseases have sandflies as vectors. Due to the increase in the number of cases of canine leishmaniasis in municipalities in the northeast region of the state of São Paulo and as the caves, apparently, are ecological niches for sandflies, the present study aimed to carry out a survey and analysis of the sand fly fauna in a visitation cave. located in Altinópolis (São Paulo, Brazil), from March 2021 to February 2022. For this, entomological captures were carried out, with specific traps called Center on Disease Control, for three consecutive nights in the second week of each month, totaling 11 months. Nine traps were installed at strategic points, with distances of approximately 10 meters from each other, at 1.5 meters above the ground. After the collections, the morphological identifications of the sandflies were made to differentiate between the species, relating the data with the capture points. The results demonstrate capture of 885 specimens, of which 353 were identified in the period from March to December 2021. Sandflies of the genus Lutzomyia, with only two species identified, corresponded to approximately half of the sample (49.57%), with the Lutzomyia longipalpis the species with the highest capture frequency (41.64%) among all the species in question and, as it is one of the main vectors of visceral leishmaniasis, this data shows epidemiological relevance. On the other hand, individuals of the genus Brumptomyia sp. also corresponded to a large part of the total (45.33%), and within this genus, Brumptomyia avellari was the predominant species (14.93%). In addition, the species Brumptomyia brumpti (11.61%) and Brumptomyia pintoi (7.65%) also stood out, among other vectors involved in the transmission cycle of the integumentary form. With social relevance, the presence of vector species of visceral and tegumentary leishmaniasis in the cave environment studied could provide an enzootic cycle and the transmission of diseases between wild animals and humans during the tourist visitation of that cave. Keywords: traps, cave, sandflies, identification, leishmaniasis, neglected tropical disease, Altinópolis, Gruta do Itambé.